2016
DOI: 10.1186/s12891-016-0954-6
|View full text |Cite
|
Sign up to set email alerts
|

Posterolateral ankle ligament injuries affect ankle stability: a finite element study

Abstract: BackgroundWe have already discovered 23 patients during the work of the outpatient department and operations whose unstable signs on the posterolateral ankle. The anterior drawer test demonstrated normal during the physical examinations while the spaces of the posterior tibiotalar joints increased in stress X-ray plain films. ATFL intact and posterolateral ligaments lax were found during operations too. It is important to make existence claims and illuminate the mechanism of posterolateral ankle instability.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The current studies con rmed that ankle joint was a joint composed of tibia, bula, talus and shin bone [9]. With an incidence of about 10%, ankle fracture was a common injury in all fractures.…”
Section: Discussionsupporting
confidence: 60%
“…The current studies con rmed that ankle joint was a joint composed of tibia, bula, talus and shin bone [9]. With an incidence of about 10%, ankle fracture was a common injury in all fractures.…”
Section: Discussionsupporting
confidence: 60%
“…With inversion loading, combined ATFL and CFL sectioning result in increased abnormal range of motion when compared with intact and ATFL‐sectioned ankles. In addition, a finite element study by Zhu et al suggested that the injury of CFL may affect posterolateral ankle stabilities. These findings might be suggestive of much more instability of the ankle for combined ATFL and CFL tear than isolated ATFL tear, which could explain our result as to why a combined ATFL and CFL tear resulted in much larger and severer cartilage degeneration than isolated ATFL tear.…”
Section: Discussionmentioning
confidence: 99%
“…30 Additionally, a finite element study reported that the injury of CFL may affect posterolateral ankle stability. 31 Abnormal kinematics consequently predispose the cartilage to degeneration and injury. 7 In our study, cartilage subregions with elevated T2 values could be found in medial and posterior regions of talar dome and medial pSTJ subregions.…”
Section: Discussionmentioning
confidence: 99%